Avaliação de vídeo educativo para promoção da saúde visual de escolares: conhecimento e atitude de professores - Melo, Karine Moreira de (2021)
The study aimed to evaluate the educational video “Visual Health for Schoolchildren” to promote teachers' knowledge and attitude about visual health care for school-age children. This is a quasi-experimental study, of the before and after type, made with Elementary School teachers. Data collection in public education units in Fortaleza/CE and its Metropolitan Region, from October 2017 to February 2018. For this purpose, teachers answered a pre-test and then watched the educational video. After a period of 15 days, they answered the post-test. Data analysis was performed using the Chi-Square and Mc Nemar statistical tests, adopting a significance level of 5% and a confidence interval of 95%. Respected ethical precepts, under opinion number 2.253.645.55 teachers participated in the study. There was a prevalence of females (94,5%), in a mean age of 39.1±8.1. In respect of professional experience, there was a predominance of two to ten years (41,8%). Regarding the degree, most had the specialization level (61,8%). Regarding training on the subject, teachers declared that they did not have specific training in the field of visual health (89,1%). In the questions about knowledge, when comparing the number of correct answers between before and after, there was a statistically significant increase in the following questions: approximate percentage of school-age children with visual problems (p=0,013); what are the refractive errors (p<0,0001); and the signs and symptoms indicative of visual difficulties, in the following items: difficulty in reading and concentrating; cover one eye trying to see better; inattention in the classroom and low grades (p<0,0001); confuses words and skips lines while reading (p=0,013); writes in large and crooked letters (p=0,001); and desinterest in studies (p=0,003). In the questions about attitude, when comparing the number of correct answers between before and after, there was a statistically significant increase in the questions: ability to identify behaviors suggestive of visual difficulty (p=0,019); and problem three situation about poor school performance and difficulty in seeing (p=0,049). Regarding the sociodemographic variables, there was no statistically significant association with the knowledge and attitude variables. Concludes that the educational video enabled teachers' knowledge and attitude about the visual health care of school-age children and could be widely used as an educational intervention, collaborating as a strategy to promote visual health.